Parallel dynamic programming - Viswanathan, V.; Huang, S.-H.S.; Hongfei Liu (Parallel and Distributed Processing, 2nd IEEE Symposium On, 1990)
Recurrence formulations for various problems such as finding an optimal order of matrix multiplication, finding an optimal binary search tree and optimal triangulation of polygons assume a similar form. A CREW PRAM algorithm has been given to solve such dynamic programming problems. The algorithm uses O(n/sup 6//log n) processors and runs in O(log/sup 2/ n)time. A modified algorithm is presented which reduces the processor requirement to O(n/sup 6//log/sup 5/n) while maintaining the same time complexity of O(log/sup 2/ n).< >